Slow-dissolving agricultural pharmaceutical covering material composition

JP2026167517APending Publication Date: 2026-10-14SANYO CHEM IND LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2026039495
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2025-03-31
Filing Date
2026-03-12
Publication Date
2026-10-14

AI Technical Summary

Benefits of technology

【0007】 本発明の徐溶性農業用薬剤用被覆材組成物は、被覆層の生分解性と薬剤の徐溶性のコントロールを高いレベルで両立し、かつ低透湿度、優れたコーティング膜の平滑性、及び流動性を有する徐溶性農業用薬剤を与えることができるという効果を奏する。 なお、本発明において「薬剤の徐溶性のコントロールに優れる」とは、薬剤の溶出速度を所望の範囲に調整可能であることを意味する。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2026167517000001
    Figure 2026167517000001
  • Figure 2026167517000002
    Figure 2026167517000002
Patent Text Reader

Abstract

The present invention provides a coating material composition for slow-dissolving agricultural chemicals that achieves a high level of control over the biodegradability of the coating layer and the slow dissolution of the chemical, while also providing a slow-dissolving agricultural chemical with excellent impact resistance, anti-adhesion properties, and fluidity. [Solution] A slow-dissolving coating material composition for agricultural chemicals containing an ester group-containing thermoplastic resin (A) and a dispersant (B), wherein the ester group-containing thermoplastic resin (A) has a number average molecular weight of 50,000 to 500,000, and the dispersant (B) is a polyester oligomer with a number average molecular weight of 1,500 to 30,000.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] This invention relates to a slow-dissolving coating material composition for agricultural chemicals. [Background technology]

[0002] In fields such as pharmaceuticals, agriculture, food additives, cosmetics, and hygiene products, slow-release agents that release active ingredients gradually are extremely useful from the standpoint of labor saving and sustained effectiveness, and are widely used. Among these, many slow-release agricultural agents (fertilizers, pesticides, and pest control agents with slow-release properties) have been proposed and are in use in which slow-release properties are achieved by coating the agricultural agent.

[0003] For example, one proposed method for imparting biodegradability to the coating layer of slow-dissolving agricultural chemicals is to add a photodegradable metal complex to a polyolefin resin (Patent Document 1). However, while these methods promote the breakdown of the coating layer, the polyolefin resin itself does not biodegrade and remains in the environment, which is a problem. [Prior art documents] [Patent Documents]

[0004] [Patent Document 1] Japanese Patent Application Publication No. 5-201786 [Overview of the project] [Problems that the invention aims to solve]

[0005] The object of the present invention is to provide a coating material composition for slow-dissolving agricultural chemicals that can achieve a high level of control over the biodegradability of the coating layer and the slow dissolution of the chemical, and that provides a slow-dissolving agricultural chemical with excellent smoothness and fluidity of the coating film. [Means for solving the problem]

[0006] The present inventors have diligently studied to solve the above problems and have arrived at the present invention. Specifically, the present invention is a slow-dissolving coating material composition for agricultural chemicals containing an ester group-containing thermoplastic resin (A) and a dispersant (B), wherein the ester group-containing thermoplastic resin (A) has a number average molecular weight of 50,000 to 500,000, and the dispersant (B) is a polyester oligomer with a number average molecular weight of 1,500 to 30,000. [Effects of the Invention]

[0007] The present invention provides a slow-dissolving agricultural chemical coating composition that achieves a high level of control over both the biodegradability of the coating layer and the slow dissolution of the chemical, while also providing a slow-dissolving agricultural chemical with low moisture permeability, excellent coating film smoothness, and fluidity. In this invention, "excellent control of the slow solubility of the drug" means that the drug dissolution rate can be adjusted to a desired range. [Modes for carrying out the invention]

[0008] <Ester group-containing thermoplastic resin (A)> The ester group-containing thermoplastic resin (A) in the present invention is a thermoplastic resin having one or more ester groups in its molecule, and from the viewpoint of biodegradability of the coating layer, aliphatic polyester resin (A1) and aliphatic-aromatic polyester resin (A2) can be suitably used.

[0009] Examples of aliphatic polyester resins (A1) include polyhydroxyalkanoic acid (A11), rosin ester resin (A12), and polycondensates of aliphatic diols and aliphatic dicarboxylic acids (A13).

[0010] Examples of polyhydroxyalkanoic acid (A11) include polylactic acid (PLA), polyglycolic acid (PGA), polyhydroxybutyrate (PHB), poly(3-hydroxybutyrate-co-3-hydroxyhexanoate) (PHBH), and polycaprolactone (PCL). Examples of the rosin ester resin (A12) include rosin esters obtained by esterifying rosins, hydrogenated rosin esters obtained by hydrogenating rosins followed by esterification, and the like.

[0011] Examples of the polycondensate (A13) of an aliphatic diol and aliphatic dicarboxylic acids include polyethylene succinate (PES), polybutylene succinate (PBS), polybutylene succinate adipate (PBSA), and polycondensates of an aliphatic diol having 2 to 6 carbon atoms, an aliphatic dicarboxylic acid having 3 to 8 carbon atoms (including the carbon of the carboxyl group), and ester-forming derivatives thereof (acid anhydrides, lower alkyl esters, acid halides, etc.), and the like. Examples of the aliphatic diol having 2 to 6 carbon atoms include ethanediol, propanediol, butanediol, dimethylpropanediol, pentanediol, hexanediol, and the like. Examples of the aliphatic dicarboxylic acid having 3 to 8 carbon atoms (including the carbon of the carboxyl group) include succinic acid, malonic acid, glutaric acid, adipic acid, suberic acid, maleic acid, fumaric acid, and the like.

[0012] The aliphatic-aromatic polyester resin (A2) is a resin obtained by replacing a part of the raw materials of the above aliphatic polyester resin (A1) with an aromatic compound, and is preferably a polyester resin having an aliphatic polyol, aromatic dicarboxylic acids, and aliphatic dicarboxylic acids as structural units, which is obtained by replacing a part of the aliphatic dicarboxylic acids in the polycondensate (A13) of the above aliphatic diol and aliphatic dicarboxylic acids with aromatic dicarboxylic acids. Examples of the aromatic dicarboxylic acid include aromatic dicarboxylic acids having 8 to 10 carbon atoms (including the carbon of the carboxyl group) (such as phthalic acid, phthalic anhydride, isophthalic acid, dimethyl isophthalate, terephthalic acid, and dimethyl terephthalate) and the like. Specific examples of (A2) include polybutylene adipate / terephthalate (PBAT), polybutylene succinate / terephthalate (PBST), polyethylene terephthalate succinate (PETS), and the like.

[0013] The number-average molecular weight (Mn) of the ester group-containing thermoplastic resin (A) in the present invention is 50,000 to 500,000. From the viewpoint of fluidity and the smoothness of the cast film of the coating composition, it is preferably 55,000 to 200,000, and more preferably 60,000 to 100,000.

[0014] The number-average molecular weight (Mn) in this invention can be measured by gel permeation chromatography, for example, under the following conditions. Device: "HLC-8120GPC" [Manufactured by Tosoh Corporation] Columns: "Guardcolumn HXL-H" (1 piece), "TSKgel GMHXL" (2 pieces) [both manufactured by Tosoh Corporation] Sample solution: 0.25% by weight tetrahydrofuran solution Solution injection volume: 100μL Flow rate: 1mL / min Measurement temperature: 40℃ Detection device: Refractive index detector Reference material: Standard polystyrene The dispersant (B) and biodegradable modifier (D), described later, can also have their number-average molecular weight (Mn) determined using a similar method.

[0015] In the present invention, the aromatic ring concentration of the ester group-containing thermoplastic resin (A) is preferably 0.001 to 2.250 mmol / g, from the viewpoint of film strength and fluidity. Preferably, (A1) and (A2) are used in combination with (A3) to achieve the aromatic ring concentration within the above range. Furthermore, the aromatic ring concentration (mmol / g) of (A) in the present invention can be determined by calculating the number of moles of aromatic rings contained in 1 g of (A).

[0016] In the present invention, the glass transition temperature of the ester group-containing thermoplastic resin (A) is preferably greater than -70°C and less than 70°C. From the viewpoint of moldability, anti-adhesion properties, and biodegradability of the coating composition, the glass transition temperature is more preferably greater than -70°C and 25°C or less, and particularly preferably greater than -70°C and 10°C or less. The glass transition temperature (°C) of (A) in this invention is a value measured and calculated by the following method.

[0017] <Methods for measuring and calculating glass transition temperature> Using a DSC measuring device, approximately 10 mg of sample (A) is heated from 20°C to 200°C at a rate of 20°C / min under a nitrogen gas flow rate of 50 mL / min [primary heating], held for 3 minutes after reaching 200°C, and then cooled to -100°C at a rate of 20°C / min. Next, the temperature is raised from -100°C to 200°C at a rate of 20°C / min [secondary heating]. The extrapolated glass transition onset temperature (Tig) (°C), which is the temperature at the intersection of a straight line extending the baseline on the low-temperature side of the DSC curve drawn during the secondary heating towards the high-temperature side and a tangent line drawn at the point where the slope of the curve of the step-like change portion of the glass transition is maximum, is defined as the glass transition temperature (°C) in this invention.

[0018] In the present invention, the ester group-containing thermoplastic resin (A) is preferably a resin with a relative crystallinity of less than 40%, or a resin with a relative crystallinity of 40% or more and a crystallization temperature of 110°C or less. If the resin has a relative crystallinity of 40% or more and a crystallization temperature greater than 110°C, the biodegradability of the coating layer deteriorates. When the relative crystallinity of (A) is 40% or more, from the viewpoint of the biodegradability of the coating material composition, the crystallization temperature of (A) is preferably 90°C or less, and more preferably 75°C or less. In this invention, the relative crystallinity (%) in (A) refers to the ratio of the weight of the crystalline portion to the total weight of the resin, and is a value measured and calculated by the following method. Furthermore, the crystallization temperature (°C) of (A) in this invention is a value measured by the following method.

[0019] <Methods for measuring and calculating relative crystallinity> Using a DSC measuring device, approximately 10 mg of sample (A) is heated from 20°C to 210°C at a rate of 10°C / min under a nitrogen gas flow rate of 50 mL / min [primary heating]. After reaching 210°C, it is held for 3 minutes, and then cooled to -100°C at a rate of 20°C / min. Next, it is heated from -100°C to 200°C at a rate of 10°C / min [secondary heating]. From the exothermic peak area during resin crystallization in the DSC curve drawn during cooling and the endothermic peak area during resin crystal melting in the DSC curve drawn during secondary heating, the heat of crystallization ΔHc and the heat of crystal melting ΔHm are obtained, respectively. Using the absolute values ​​of ΔHc and ΔHm, the relative crystallinity (%) is calculated from the following formula. Relative crystallinity (%) = {(|ΔHm|-|ΔHc|) / ΔHm} × 100

[0020] <Method for measuring crystallization temperature> Using a DSC measuring device, in accordance with JIS K7121, 10 mg of sample (A) is heated from 30°C to 200°C at a heating rate of 20°C / min under conditions of a nitrogen gas flow rate of 50 mL / min, held for 3 minutes after reaching 200°C, and then cooled from 200°C to 30°C at a cooling rate of 20°C / min. The crystallization peak temperature (Tpc), which is the temperature at the peak of the crystallization peak, is defined as the crystallization temperature (°C) in this invention.

[0021] Solubility parameter (SP) of ester group-containing thermoplastic resin (A) in the present invention A ) is 9.1~11.5 (cal / cm³) from the viewpoint of the dispersibility of the dispersant (B) in (A). 3 ) 1 / 2 Preferably, it is 9.1 to 11.1 (cal / cm²). 3 ) 1 / 2 That is the case. Furthermore, the solubility parameters in this invention (the same applies to the solubility parameters (also called SP values) of components other than (A) described later) refer to the values ​​calculated using formula (28) on page 153 of the Fedors method [Polymer Engineering and Science, February, 1974, Vol. 14, No. 2, pp. 147-154], using the numerical values ​​(heat of vaporization and molar volume of atoms or functional groups at 25°C) described on page 152 (Table 5).

[0022] In the present invention, the ester group concentration of the ester group-containing thermoplastic resin (A) is preferably 0.1 g / g or more and 0.6 g / g or less based on the weight of (A), from the viewpoint of biodegradability and moisture permeability of the coating material composition. The ester group concentration (g / g) of (A) can be calculated from the number of ester groups [-C(=O)O-] in (A), and is defined as the weight (g) of ester groups present in 1g of (A). The actual ester group concentration (g / g) can be calculated by measuring infrared spectroscopy (IR) of (A) and using the intensity of the peak derived from the ester groups and a calibration curve (a plot of the relationship between peak intensity and ester group concentration) created using a sample with a known ester group concentration. Alternatively, (A) and an equivalent weight of deionized water can be placed in an autoclave and reacted at 180°C for 6 hours to hydrolyze the ester groups in (A). After the reaction, the acid value and hydroxyl value of (A) are measured, and the ester group concentration in (A) can be calculated based on the acid value and hydroxyl value. Furthermore, the ester group concentration (g / g) of (A) can be calculated by determining the number of ester groups [-C(=O)O-] present in (A) from the ratio of the raw materials used in the production of (A).

[0023] The ester group-containing thermoplastic resin (A) in the present invention is a biodegradable resin in which the ester bonds in the molecule are hydrolyzed by moisture in the environment, resulting in a low molecular weight resin, and is further degradable by microorganisms, enzymes, or ingestion by living organisms, and is preferably a resin that can ultimately be decomposed into water and carbon dioxide.

[0024] <Dispersant (B)> The dispersant (B) in the present invention is a polyester oligomer with a number average molecular weight of 1500 to 30000. The number average molecular weight of the dispersant (B) is preferably 1800 to 10000, and more preferably 2000 to 5000.

[0025] As for (B), aliphatic polyester oligomer (B1) and aliphatic-aromatic polyester oligomer (B2) can be suitably used.

[0026] Examples of aliphatic polyester oligomers (B1) include polyhydroxyalkanoic acid oligomers (B11), rosin ester oligomers (B12), and polycondensate oligomers of aliphatic diols and aliphatic dicarboxylic acids (B13).

[0027] Examples of polyhydroxyalkanoic acid oligomers (B11) include polylactic acid (PLA) oligomers, polyglycolic acid (PGA) oligomers, polyhydroxybutyrate (PHB) oligomers, poly(3-hydroxybutyrate-co-3-hydroxyhexanoate) (PHBH) oligomers, and polycaprolactone (PCL) oligomers. Examples of rosin ester oligomers (B12) include rosin ester oligomers obtained by esterifying rosins and hydrogenated rosin ester oligomers obtained by hydrogenating and esterifying rosins.

[0028] Examples of polycondensation oligomers of aliphatic dicarboxylic acids (B13) include oligomers of polyethylene succinate (PES), polybutylene succinate (PBS), polybutylene succinate adipate (PBSA), and polycondensation oligomers of aliphatic diols having 2 to 6 carbon atoms and aliphatic dicarboxylic acids having 3 to 8 carbon atoms (including the carbon atoms of the carboxyl group), as well as ester-forming derivatives thereof (acid anhydrides, lower alkyl esters, acid halides, etc.). Examples of aliphatic diols having 2 to 6 carbon atoms include ethanediol, propanediol, butanediol, dimethylpropanediol, pentanediol, and hexanediol. Aliphatic dicarboxylic acids with 3 to 8 carbon atoms (including the carbon atoms of the carboxyl group) include succinic acid, malonic acid, glutaric acid, adipic acid, suberic acid, maleic acid, and fumaric acid.

[0029] The aliphatic-aromatic polyester oligomer (B2) is obtained by replacing a portion of the raw materials of the above aliphatic polyester oligomer (B1) with aromatic compounds, and preferably, a portion of the aliphatic dicarboxylic acids in the polycondensate oligomer (B13) of the above aliphatic diol and aliphatic dicarboxylic acids is replaced with aromatic dicarboxylic acids, and is a polyester oligomer having aliphatic polyol, aromatic dicarboxylic acids and aliphatic dicarboxylic acids as constituent units.

[0030] Examples of aromatic dicarboxylic acids include aromatic dicarboxylic acids with 8 to 10 carbon atoms (including the carbon atoms of the carboxyl group) (e.g., phthalic acid, phthalic anhydride, isophthalic acid, dimethylisophthalic acid, terephthalic acid, and dimethylterephthalic acid). Specific examples of (B2) include oligomers of polybutylene adipate / terephthalate (PBAT), oligomers of polybutylene succinate / terephthalate (PBST), and oligomers of polyethylene terephthalate succinate (PETS).

[0031] <Slowly soluble agricultural drug coating composition (X)> The slow-dissolving agricultural chemical coating composition (X) of the present invention is a slow-dissolving agricultural chemical coating composition containing the ester group-containing thermoplastic resin (A) and the dispersant (B). The weight ratio of (A) to the dispersant (B) in the coating composition [(A) / (B)] is preferably 99 / 1 to 70 / 30, more preferably 90 / 10 to 70 / 30, and particularly preferably 85 / 15 to 70 / 30, from the viewpoint of achieving both biodegradability of the coating composition and slow dissolution of the chemical.

[0032] The melt flow rate (MFR) of the slow-dissolving agricultural chemical coating composition (X) of the present invention at 190°C under a 10 kg load is in the range of 0.01 to 300 g / 10 min. More preferably, it is 0.03 to 200 g / 10 min, and even more preferably, 0.05 to 100 g / 10 min.

[0033] The melt flow rate (MFR) in this invention was measured using a melt indexer under the following conditions. Equipment: ["Melt Indexer F-F01", manufactured by Toyo Seiki Co., Ltd.] Temperature: 190℃ Load capacity: 10kg

[0034] The slow-dissolving agricultural chemical coating composition (X) of the present invention may further contain, in addition to (A) and (B) above, an organic layered silicate (C) as described later. It may also further contain a biodegradability modifier (D).

[0035] <Organic layered silicate (C)> Examples of organic layered silicate (C) in the present invention include organic layered silicate (C) which has organic compounds between layers and / or has organic groups on its surface.

[0036] Examples of layered silicates constituting organic layered silicate (C) include talc, smectite minerals {bentonite (including those purified to contain only the main component montmorillonite), hectorite, fluoride hectorite, and saponite, etc.}, mica, vermiculite, and brittle mica. Smectite minerals with interlayer charges (montmorillonite, hectorite, fluoride hectorite, and saponite, etc.), mica, vermiculite, and brittle mica are particularly preferred.

[0037] Examples of layered silicates having organic compounds between the layers include organic layered silicates (C1), in which the interlayer metal ions of the layered silicate are ion-exchanged with organic cations, and organic layered silicates (C2), in which polyether compounds are found between the layers of the layered silicate. Examples of layered silicates having organic groups on their surface include organically modified layered silicates (C3), which are obtained by surface-modifying a layered silicate by reacting it with a coupling agent having both organic and reactive functional groups.

[0038] Examples of organic cations constituting the aforementioned organic layered silicate (C1) include primary ammonium ions, secondary ammonium ions, tertiary ammonium ions, amino acid derivatives, quaternary ammonium ions, organic phosphonium ions, organic pyridinium ions, and organic sulfonium ions.

[0039] Examples of primary ammonium ions include octylammonium ion, laurylammonium ion, tetradecylammonium ion, hexadecylammonium ion, stearylammonium ion, oleylammonium ion, benzylammonium ion, and anilinium ion. Examples of secondary ammonium ions include dilaurylammonium ion, ditetradecylammonium ion, dihexadecylammonium ion, distearylammonium ion, and N-methylanilinium ion. Examples of tertiary ammonium ions include dimethyloctylammonium ion, dimethyldecylammonium ion, dimethyllaurylammonium ion, dimethylmyristylammonium ion, dimethylpalmitylammonium ion, dimethylstearylammonium ion, dilaurylmonomethylammonium ion, tributylammonium ion, trioctylammonium ion, and N,N-dimethylanilinium ion. Examples of amino acid derivatives include the ammonium ion of 12-aminolaurylcarboxylic acid, the ammonium ion of N,N-dimethyl-6-aminohexylcarboxylic acid, the ammonium ion of Nn-dodecyl-N,N-dimethyl10-aminodecylcarboxylic acid, and the ammonium ion of dimethyl-N-12-aminolaurylcarboxylic acid.

[0040] Specific examples of quaternary ammonium ions include dodecyltrimethylammonium ion, lauryltrimethylammonium ion, hexadecyltrimethylammonium ion, dodecylammonium ion, dimethyldistearylammonium ion, benzyldimethylstearylammonium ion, dialkyldimethylammonium ion, tetrabutylammonium ion, tetrapentylammonium ion, tetraethylammonium ion, and triethylmethylammonium ion.

[0041] Examples of organic phosphonium ions include phosphonium ions in which the nitrogen atom of the above-mentioned quaternary ammonium ion is replaced by a phosphorus atom.

[0042] The above organic cations may be a single type or a mixture of two or more types. From the viewpoint of affinity with (A), water vapor permeability of the resin composition, and safety, quaternary ammonium ions are preferred.

[0043] The method for obtaining organically modified layered silicate (C1), obtained by ion-exchanging the interlayer metal ions of layered silicate with organic cations, is not particularly limited and can be obtained by known methods. For example, it can be obtained by immersing layered silicate in water, an organic solvent, or a mixed solvent of water and an organic solvent, adding and stirring a salt containing organic cations, letting it stand for a certain period of time, filtering, washing and drying the resulting solid. The salt containing organic cations may be generated in situ; for example, a salt containing primary ammonium ions may be generated in situ by adding a primary amine and hydrochloric acid to obtain (C1). Furthermore, commercially available organically modified layered silicate, obtained by ion-exchanging the interlayer metal ions of layered silicate with organic cations, may be used.

[0044] In a method for obtaining organic layered silicate (C1) by ion exchange of interlayer metal ions in layered silicate with organic cations, the salt containing organic cations used is preferably a salt of an organic cation and a counterion (anion). From the viewpoint of reducing environmental impact, chloride ions, bromide ions, and acetate ions are preferred as counterions.

[0045] Examples of polyether compounds constituting the organic layered silicate (C2) having polyether compounds between the layers of the aforementioned layered silicate include polyethylene glycol and nonionic surfactants having polyoxyethylene groups. Examples of nonionic surfactants having polyoxyethylene groups include polyoxyethylene alkyl ethers, polyoxyethylene phenyl ethers, polyoxyethylene / polyoxypropylene block polymers, fatty acid polyethylene glycols, fatty acid polyoxyethylene sorbitan, and polyoxyethylene alkylamino ethers.

[0046] The method for obtaining the above-mentioned organic layered silicate (C2) is not particularly limited and can be obtained by known methods. For example, it can be obtained by immersing the layered silicate in water, an organic solvent, or a mixed solvent of water and an organic solvent (preferably a polar solvent such as alcohol, glycol, ketone, ether, or amide), then adding and stirring a polyether compound, letting it stand for a certain period of time, and then spray drying. Alternatively, organic layered silicate (C2) obtained by treating layered silicate with a polyether compound, or commercially available products, may be used.

[0047] In (C2), the amount of polyether compound by weight per 100 parts by weight of layered silicate is preferably 0.1 to 50 parts by weight, more preferably 1 to 40 parts by weight, from the viewpoint of water vapor permeability and slow solubility of the drug when used as a coating layer for a slow-solubility drug.

[0048] The organic layered silicate (C3), obtained by surface-modifying the layered silicate with a coupling agent having an organic group and a reactive functional group, is an organic layered silicate obtained by surface-modifying a layered silicate with a coupling agent having an organic group and a reactive functional group, and has an organic group derived from the coupling agent as an organic group portion on the surface of the layered silicate.

[0049] Examples of coupling agents having the above-mentioned organic group and reactive functional group include isocyanate compounds, organosilane compounds, organotitanate compounds, organoborane compounds, and epoxy compounds. Of these, organosilane compounds are particularly preferred from the viewpoint of reactivity with layered silicates, and specific examples include γ-glycidoxypropyltrimethoxysilane, γ-glycidoxypropyltriethoxysilane, and β-(3,4-epoxycyclohexyl )Epoxy group-containing alkoxysilane compounds such as ethyltrimethoxysilane, mercapto group-containing alkoxysilane compounds such as γ-mercaptopropyltrimethoxysilane and γ-mercaptopropyltriethoxysilane, ureido group-containing alkoxysilane compounds such as γ-ureidopropyltriethoxysilane, γ-ureidopropyltrimethoxysilane, and γ-(2-ureidoethyl)aminopropyltrimethoxysilane, γ-isocyanatopropyltriethoxysilane, γ-isocyanatopropyltrimethoxysilane, γ-isocyanatopropylmethyldimethoxysilane, γ-isocyanatopropylmethyldiethoxysilane, γ-isocyanatopropylethyldimethoxysilane, γ-isocyanatopropylethyldiethoxysilane, γ-isocyanatopropyl Examples include isocyanate group-containing alkoxysilane compounds such as pyrtrichlorosilane, amino group-containing alkoxysilane compounds such as γ-(2-aminoethyl)aminopropylmethyldimethoxysilane, γ-(2-aminoethyl)aminopropyltrimethoxysilane, and γ-aminopropyltrimethoxysilane, hydroxyl group-containing alkoxysilane compounds such as γ-hydroxypropyltrimethoxysilane and γ-hydroxypropyltriethoxysilane, and carbon-carbon unsaturated group-containing alkoxysilane compounds such as γ-methacryloxypropyltrimethoxysilane, vinyltrimethoxysilane, and N-β-(N-vinylbenzylaminoethyl)-γ-aminopropyltrimethoxysilane hydrochloride, with carbon-carbon unsaturated group-containing alkoxysilane compounds being the most preferred.

[0050] The method for obtaining organically modified layered silicate (C3) by surface modification of the above-mentioned layered silicate with a coupling agent having an organic group and a reactive functional group is not particularly limited, but includes: (1) a method of adsorbing the coupling agent onto the layered silicate in a polar solvent such as water, methanol, ethanol, or a mixture thereof; (2) a method of adding the layered silicate to a high-speed stirring mixer such as a Henschel mixer and adsorbing the coupling agent or a solution of the coupling agent (a solution of the coupling agent diluted with water or a mixture of water and an organic solvent) dropwise while stirring; and (3) a method of directly adding the coupling agent to the layered silicate and adsorbing it by mixing it in a mortar and pestle or the like. When reacting the layered silicate with the coupling agent, it is preferable to simultaneously mix water, acidic water, alkaline water, etc., to promote the hydrolysis of the alkoxy group of the coupling agent. In addition, in order to increase the reaction efficiency of the coupling agent, an organic solvent that dissolves both water and the coupling agent, such as methanol or ethanol, may be mixed in addition to water. It is also possible to further promote the reaction by heat-treating the layered silicate treated with such a coupling agent. Alternatively, a method may be used in which the layered silicate and the coupling agent are not reacted beforehand, but rather the coupling agent is added together when the layered silicate and thermoplastic resin (A), etc., are melt-kneaded; this is known as the integral blend method.

[0051] Furthermore, by performing both ion exchange of interlayer metal ions in layered silicates with organic cations and a reaction with a coupling agent having organic groups and reactive functional groups, it is possible to obtain layered silicates that have organic compounds between layers and organic groups on their surface.

[0052] Among organically modified layered silicates (C3), from the viewpoint of water vapor permeability of the resin composition, an organically modified layered silicate (C3) having an organic group with 6 or more carbon atoms on its surface is preferable, and an organically modified layered silicate (C3) having an organic group with 6 or more carbon atoms on its surface is more preferable. Examples of the organic group with 6 or more carbon atoms include alkyl groups with 6 or more carbon atoms, alkylene groups with 6 or more carbon atoms, aromatic ring groups (aryl groups which may have an alkyl group as a substituent), and the like, and alkyl groups with 6 or more carbon atoms, aromatic ring groups and the like are preferred. The number of carbon atoms in the organic group moiety is more preferably 10 or more, and particularly preferably 20 or more. Further, from the viewpoints of water vapor permeability and hygroscopicity, a layered silicate having an organic compound between layers of the layered silicate is also preferable, and an organically modified layered silicate (C1) having quaternary ammonium ions between layers is more preferable. A layered silicate which has an organic compound between layers and has an organic group with 6 or more carbon atoms on the surface is also preferable.

[0053] Further, the organically modified layered silicate (C) in the present invention, from the viewpoint of moldability of the resin composition, preferably has a swelling power in chloroform of 70 mL / 2g or less, more preferably 10 to 60 mL / 2g, as measured by changing water to chloroform in the standard test method of Japan Bentonite Industry Association: Swelling Test Method for Bentonite (Powder) (JBAS104:77). The swelling power in chloroform measured by changing water to chloroform in JBAS104:77 can be specifically measured as follows.

[0054] <Method for measuring swelling power in chloroform, measured by changing water to chloroform in JBAS104:77 (Swelling Test Method for Bentonite (Powder))> 2.0 g of the organically modified layered silicate (C) is added little by little to a 100 mL stoppered graduated cylinder containing 100 mL of chloroform. At this time, the next addition is performed after the added (C) has deposited on the bottom of the graduated cylinder. After the final addition, the mixture is allowed to stand at 25°C for 24 hours, then the apparent volume of the swollen mass of the organically modified layered silicate (C) at the bottom of the graduated cylinder is read from the scale of the graduated cylinder, and this value is expressed as the swelling power (mL / 2g) in chloroform.

[0055] The modification rate (%) in organically modified layered silicate (C) is preferably 0.1 to 50%, and more preferably 10 to 45%, from the viewpoint of water vapor permeability and slow solubility of the drug when used as a coating layer for a slow-solubility drug. The above modification rate (%) refers to the proportion of the surface of the layered silicate that has been organically modified in organically modified layered silicate (C), that is, the percentage of the area modified (coated) with organic groups relative to the area of ​​the layered silicate, and is a value measured and calculated by the following method.

[0056] <Method for measuring and calculating the modification rate (%) of (C)> Organic layered silicate (C) in toluene in a solution of 1.0 × 10⁻⁶ -3 Samples dispersed at a mass percent concentration, spin-cast onto a mica substrate, and dried were observed using a tapping mode AFM (Atomic Force Microscope) (Seiko Instruments Inc., SPA-300). From the obtained images, the area modified (coated) with organic groups on the layered silicate surface was analyzed, and the modification rate (%) was calculated using the following formula. Modification rate (%) = Area modified (coated) with organic groups / Total area of ​​layered silicate × 100

[0057] The state of modification by organic groups can be determined by considering that the region showing a significant height (thickness) (1 nm or more) from the surface of the layered silicate is modified by organic groups. Specifically, the modification rate can be calculated as follows: The height and area of ​​the layered silicate are determined using Grain Size, an analytical tool within an atomic force microscope. After calculating the total area of ​​the layered silicate, any portion significantly higher than the surface height of the layered silicate is considered to be the portion modified (coated) with organic groups, and the area modified (coated) with organic groups is calculated. The modification rate (%) is calculated by substituting these values ​​into the above formula.

[0058] The median diameter of the organic layered silicate (C) is preferably 0.01 to 40 μm, from the viewpoint of the water vapor permeability of the resin composition and the ease of adjusting the slow solubility of the drug when used as a coating layer for a slow-solubility drug. In the present invention, the median diameter (μm) is a value measured using a laser diffraction / scattering particle size distribution analyzer (LA-300, manufactured by Horiba, Ltd.) with trichloroethylene as the dispersion medium and without ultrasonic irradiation. The median diameter of the organic layered silicate (C) in the resin composition of the present invention can be measured by the following method.

[0059] <Median diameter of organic layered silicate (C) in resin composition> The resin composition is dissolved in a suitable solvent (e.g., DMF, or a chlorine-based solvent such as trichloroethylene), and the inorganic material is recovered by centrifugation. At this point, the mixture contains both organically modified layered silicate (C) and unorganized (non-organic) layered silicate. The inorganic material is dissolved and dispersed in a chlorine-based solvent (e.g., trichloroethylene), and the supernatant is collected. Since the unorganized layered silicate does not disperse in the chlorine-based solvent (e.g., trichloroethylene), only the organically modified layered silicate (C) is recovered. The recovered organically modified layered silicate (C) is dispersed in trichloroethylene as a dispersion medium in the same manner as above, and measured using a laser diffraction / scattering particle size distribution analyzer.

[0060] The weight of (C) above is preferably 20-50% by weight, and more preferably 30-45% by weight, based on the total weight of (A) and (B).

[0061] <Biodegradable regulator (D)> The slow-dissolving agricultural chemical coating composition (X) of the present invention preferably contains a biodegradability modifier (D) from the viewpoint of biodegradability. Examples of biodegradable modifiers (D) include wax (D3) [sometimes referred to as biodegradable modifier (D3)].

[0062] Examples of waxes (D3) include natural oils and fats (D31) and ester waxes (D32).

[0063] Examples of natural oils and fats (D31) include hydrogenated jojoba oil, castor wax (hydrogenated castor oil), hydrogenated rice oil, hydrogenated coconut oil, hydrogenated soybean oil, hydrogenated rapeseed oil, hydrogenated palm oil, hydrogenated beef tallow oil, and hydrogenated lard oil. Castor wax is particularly preferred as (D31) because it has moderate biodegradability and effectively reduces humidity when dispersed in (A).

[0064] Examples of ester waxes (D32) include plant-based natural waxes {candelilla wax, carnauba wax, rice bran wax, wood wax, etc.}, animal-based natural waxes {beeswax, shellac wax, lanolin wax, and whale wax, etc.}, mineral-based natural waxes {montan wax, ozokerite, and ceresin, etc.}, and their refined products, as well as those synthesized from carboxylic acids with 2 to 34 carbon atoms (including the carbon atoms of the carboxyl group) and alcohols with 1 to 36 carbon atoms. As for (D32), candelilla wax, carnauba wax, rice wax, and beeswax are particularly preferred because they have moderate biodegradability and effectively reduce moisture permeability when dispersed in (A).

[0065] When the coating composition of the present invention contains a wax (D3) containing a fatty acid and a fatty acid ester, the melting point of (D3) is preferably 90°C or lower, from the viewpoint of adjusting the melt viscosity or solution viscosity of the coating composition and improving effects such as improved dispersibility, prevention of adhesion of slow-dissolving agricultural chemicals, and fluidity. Furthermore, from the viewpoint of preventing (D3) from bleeding out onto the surface of slow-dissolving agricultural chemicals, which can cause stickiness and adhesion, it is preferable that the melting point of (D3) be 40°C or higher. That is, it is preferable that the melting point of (D3) be 40 to 90°C.

[0066] The weight of (D) is preferably 10 to 100% by weight, more preferably 20 to 80% by weight, based on the total weight of (A) and (B).

[0067] The slow-dissolving agricultural chemical coating composition (X) of the present invention may contain other additives (E) as needed, as long as they do not impair the effects of the present invention. Examples of other additives (E) include slow-dissolving modifiers other than the organic clay (E1), organic fillers (E2), inorganic fillers (E3), water-absorbing resin particles, lubricants, plasticizers, thixotropic agents, foaming agents, ultraviolet absorbers, antioxidants, colorants, flame retardants, fungicides, anti-settling agents, and defoaming agents.

[0068] The slow-dissolving agricultural chemical coating composition (X) of the present invention may optionally contain a slow-dissolving modifier (E1) other than the organic clay, for the purpose of lowering the moisture permeability of the coating composition and adjusting the slow-dissolving properties of the chemical (extending the number of days for slow dissolution). Specific examples of the slow-dissolving modifier (E1) other than the organic clay include hydrophobic wax (E11), hydrophobic plasticizer (E12), carbodiimide compounds (E13), oxazoline compounds (E14), isocyanate compounds (E15), and epoxy compounds (E16).

[0069] Examples of hydrophobic waxes (E11) include hydrocarbon compounds and metal soaps (aluminum stearate, calcium stearate, etc.) with a number-average molecular weight of 300 to 2000. Specific examples of hydrocarbon compounds with a number average molecular weight of 300 to 2000 include paraffin (including eicosane, henicosane, tetracosane, triacontane, etc.), polycyclic aromatic hydrocarbons (including benzopyrene, polyacene, etc.), and low molecular weight polyolefins (low molecular weight polyethylene, etc.). Petroleum waxes with hydrocarbon compounds as the main component (including paraffin wax, microcrystalline wax, petrolatum, etc.) can also be used. When the slow-dissolving agricultural chemical coating composition (X) of the present invention contains a hydrocarbon compound with a number average molecular weight of 300 to 2000, it is preferable that the slow-dissolving properties of the chemical are easily adjusted (the number of days required for slow dissolving is easily extended), as well as that the anti-adhesion and fluidity of the slow-dissolving agricultural chemical are easily improved. Furthermore, when the hydrocarbon compound has a number average molecular weight of 300 to 1500, it is also good from the viewpoint of biodegradability.

[0070] Examples of hydrophobic plasticizers (E12) include low molecular weight aliphatic polyesters with a weight-average molecular weight of 20,000 or less {succinic acid and ethylene glycol / propylene glycol condensate (for example, trade name "Polysizer", manufactured by Dainippon Ink, Inc.), excluding those falling under (A) above} and oils and fats not falling under (D3) above.

[0071] Examples of carbodiimide compounds (E13) include poly(4,4'-diphenylmethanecarbodiimide), poly(p-phenylenecarbodiimide), poly(m-phenylenecarbodiimide), poly(tolylcarbodiimide), poly(diisopropylphenylenecarbodiimide), poly(methyl-diisopropylphenylenecarbodiimide), and poly(triisopropylphenylenecarbodiimide). Commercially available carbodiimide compounds include "Stavaxol" from Rhein Chemie and "Carbodilite" from Nisshinbo Inc.

[0072] Examples of oxazoline compounds (E14) include monooxazoline compounds such as 2-methyl-2-oxazoline, 2-ethyl-2-oxazoline, 2-phenyl-2-oxazoline, 2-isopropenyl-2-oxazoline, and 2,4-dimethyl-2-oxazoline; bisoxazoline compounds such as 2,2'-(1,3-phenylene)bis(2-oxazoline); and polymers having an oxazoline group in the side chain.

[0073] Examples of isocyanate compounds (E15) include hexamethylene diisocyanate, 2,4-tolylene diisocyanate, 2,6-tolylene diisocyanate, xylylene diisocyanate, and diphenylmethane diisocyanate.

[0074] Examples of epoxy compounds (E16) include ethylene glycol diglycidyl ether, polyethylene glycol diglycidyl ether, propylene glycol diglycidyl ether, polypropylene glycol diglycidyl ether, polybutadiene diglycidyl ether, neopentyl glycol diglycidyl ether, 1,6-hexanediol diglycidyl ether, cyclohexanedimethanol diglycidyl ether, hydroquinone diglycidyl ether, N-glycidylphthalimide, hydrogenated bisphenol A diglycidyl ether, sorbitol polyglycidyl ether, and pentaerythritol. Examples include tall polyglycidyl ether, glycerol polyglycidyl ether, polyglycerol polyglycidyl ether, trimethylpropane polyglycidyl ether, 2-ethylhexyl glycidyl ether, phenyl glycidyl ether, phenyl (polyethylene glycol) glycidyl ether, phenyl (polypropylene glycol) glycidyl ether, p-tert-butylphenyl glycidyl ether, diglycidyl-o-phthalate, diglycidyl terephthalate, dibromophenyl glycidyl ether, epoxidized vegetable oil, and polymers having glycidyl groups in their side chains.

[0075] The slow-dissolving agricultural chemical coating composition (X) of the present invention may optionally contain an organic filler (E2) for the purpose of improving the biodegradability of the coating composition and adjusting the slow dissolution of the chemical (shortening the number of days required for slow dissolution). Specific examples of the organic filler (E2) include starch such as corn starch, modified starch, agar, and xanthones.

[0076] The slow-dissolving agricultural chemical coating composition (X) of the present invention may contain an inorganic filler (E3). Specific examples of the inorganic filler (E3) include talc, mica, bentonite, clay, calcium carbonate, silica, diatomaceous earth, metal oxides such as titanium dioxide, and sulfur powder. The total content of other additives (E) is preferably 80% by weight or less, more preferably 50% by weight or less, and preferably 5% by weight or more, based on the total weight of (A) and (B).

[0077] The method for producing the slow-dissolving agricultural chemical coating composition (X) of the present invention is not particularly limited, but it can be obtained by mixing (A), (B), optionally (C), (D), and other additives (E) in or without a solvent. When mixing in the presence of a solvent, the solvent is preferably an organic solvent. Suitable organic solvents include chlorinated solvents (e.g., trichloroethylene, methylene chloride, dichloroethane, tetrachloroethylene, and chloroform), ketone solvents (e.g., methyl ethyl ketone and methyl isobutyl ketone), aromatic solvents (e.g., benzene, toluene, xylene, and orthodichlorobenzene), amide solvents (N,N-dimethylacetamide and N,N-dimethylformamide), and mixtures thereof. The amount of solvent used is not particularly limited, but 0.6 to 1.4 L, 0.7 to 1.3 L, or 0.8 to 1.2 L is used per 100 g of the total weight of (A) and (B), (C) and (D) added as needed, and other additives (E). When mixing in the absence of a solvent, one method is to heat (A) to a temperature at which it melts and then knead it using a kneading device or the like. However, the solvent may be present when kneading with a kneading device or the like.

[0078] The composition is in the form of a solution or dispersion obtained by mixing (A), (B), (C), (D) as needed, and other additives (E) in the presence of a solvent, or a solid molded body obtained by drying the solution or dispersion as needed. The molded body may be in the form of a film or granules. To make it into a film, the solution or dispersion can be cast and then the solvent can be dried. To make it into granules, the solution or dispersion can be spray-dried. Alternatively, as described above, the slow-dissolving agricultural chemical coating composition (X) can also be obtained by mixing in the absence of a solvent, in which case the slow-dissolving agricultural chemical coating composition (X) becomes a granular molded body (pellet). To obtain a film-like molded body from a granular molded body, the granular molded body (pellet) can be heat-pressed or otherwise used. There are no particular restrictions on the conditions for heat pressing, but for example, around 180°C for about 1 minute is preferable.

[0079] The slow-dissolving coating composition (X) for agricultural chemicals of the present invention is useful for agricultural chemical applications, particularly as a coating layer (L) for agricultural chemicals (F) sprayed on fields and paddy fields.

[0080] <Slow-release agricultural chemical (Y)> The slow-dissolving agricultural agent (Y) of the present invention is a slow-dissolving agricultural agent in which at least a portion of the surface of an agricultural agent (F) is covered with one or more coating layers (L), wherein at least one of the one or more coating layers contains a coating layer (L) made of the above-mentioned slow-dissolving agricultural agent coating material composition. The agricultural agent (F) may be used alone or in combination of two or more types. In this specification, "at least a portion of the surface of the agricultural agent (F) is covered with a coating layer" includes not only the direct covering of the surface of the agricultural agent (F) by the coating layer, but also covering it with another layer such as a protective layer interposed therebetween.

[0081] The average film thickness (μm) of the above-mentioned coating layer (L) is preferably 10 to 150 μm, and particularly preferably 10 to 130 μm, from the viewpoint of controlling gradual dissolution, productivity and cost, and preventing peeling of the coating layer. The average film thickness (μm) of the coating layer (L) in this invention can be measured by the following method.

[0082] <Method for measuring the average film thickness of the coating layer (L)> The slow-dissolving agricultural agent (Y) of the present invention is cut in half with a razor blade so as to pass through its center of gravity, the cross-section is photographed with a scanning electron microscope (SEM), and the thickness (μm) of the coating layer (L) at any one location is measured. Five particles are randomly selected and cut as described above, and the thickness of the coating layer (L) is measured. The average value of the coating layer (L) thicknesses of the five particles is taken as the average film thickness (μm) of the coating layer (L).

[0083] In the slow-dissolving agricultural agent (Y) of the present invention, the amount of agricultural agent (F) per 100 parts by weight of the coating material composition for the slow-dissolving agricultural agent is preferably 300 parts by weight or more and 900 parts by weight or less, more preferably 380 parts by weight or more and 900 parts by weight or less, more preferably 500 parts by weight or more and 900 parts by weight or less, more preferably 750 parts by weight or more and 900 parts by weight or less, and more preferably 780 parts by weight or more and 850 parts by weight or less. Note that the weight of agricultural agent (F) having a protective layer on its surface is calculated excluding the weight of the protective layer. In one embodiment of the present invention, the weight of the protective layer relative to the weight of agricultural agent (F) is preferably 0.5 to 18.8% by weight or 1.1 to 13.3% by weight.

[0084] Examples of agricultural chemicals (F) include fertilizers, pesticides (fungicides, herbicides, and plant growth regulators, etc.), and pest control agents (repellents, insecticides, acaricides, and rodenticides, etc.). As fertilizer, known granular chemical fertilizers can be used. Specific examples include nitrogen fertilizers, phosphate fertilizers, potassium fertilizers, calcium salts, magnesium salts, iron salts, and combinations of two or more of these. In addition, fertilizers having a protective layer made of waxes (at least one of paraffin wax, rice wax, and ester wax, etc.) on the surface of the above agricultural chemical (F) can also be used. If the components contained in the protective layer present on the surface, or the entire protective layer, are a biodegradable regulator (D1) having at least one functional group selected from the group consisting of ester groups, urethane groups, and amide groups, or a biodegradable regulator (D2) having a carboxyl group, then the components and the entire protective layer shall be considered to fall under the category of a biodegradable regulator (D1) or a biodegradable regulator (D2) having a carboxyl group in the case of a slow-dissolving agricultural agent. In one embodiment of the present invention, the components contained in the protective layer, or the entire protective layer, do not have at least one functional group selected from the group consisting of ester groups, urethane groups, and amide groups, and do not have a carboxyl group.

[0085] The thickness of the protective layer is preferably 3 to 100 μm, and particularly preferably 5 to 70 μm, from the viewpoint of controlling gradual dissolution, productivity, and cost. The method for measuring the thickness is the same as the method for measuring the thickness of the coating layer (L). The protective layer can be prepared by dissolving or dispersing the components that form the protective layer in an organic solvent, spraying it onto the fertilizer, and then drying it. By forming a coating layer (L) on this, the slow-dissolving agricultural agent (Y) of the present invention is obtained.

[0086] Nitrogen fertilizers are fertilizers that contain nitrogen-containing compounds as their main component and are not particularly limited, but examples include urea, aldehyde condensed ureas such as formaldehyde condensed urea and isobutyraldehyde condensed urea, guanylurea sulfates, calcium cyanamide, ammonium nitrate, ammonium sulfate, and ammonium chloride. Examples of phosphate fertilizers, though not particularly limited, include ammonium dihydrogen phosphate, superphosphate, double superphosphate, fused phosphate fertilizer, and calcined phosphate fertilizer. Potassium fertilizers are fertilizers whose main component is potassium, and are not particularly limited, but examples include potassium nitrate, potassium chloride, potassium sulfate, and potassium silicate. Examples of calcium salts include calcium phosphate, calcium sulfate, calcium nitrate, and calcium chloride. Examples of magnesium salts include magnesium nitrate, magnesium chloride, magnesium sulfate, and magnesium phosphate. Examples of iron salts include ferrous nitrate, ferric nitrate, ferrous phosphate, ferric phosphate, ferrous sulfate, ferric sulfate, ferrous hydrochloride, and ferric hydrochloride.

[0087] For agricultural chemicals (F), granular form is preferred. In that case, the weight-average particle size is preferably 1 mm to 20 mm, and more preferably 2 mm to 10 mm. Furthermore, a carrier that holds the agricultural chemical (F) may be used. Examples of carriers include kaolinite and other kaolin minerals; mineral carriers such as montmorillonite, smectite, talc, pyrophyllite, silica, hydrated calcium silicate, calcium carbonate, and zeolite; plant-based carriers such as cellulose, starch, and soy flour; and water-soluble carriers such as lactose, sucrose, and dextrin.

[0088] The slow-dissolving coating layer for agricultural chemicals and the slow-dissolving agricultural chemicals of the present invention can be manufactured by combining known methods. For example, when manufacturing the slow-dissolving coating material composition for agricultural chemicals described above, a solution or dispersion obtained by mixing (A), (B), (C), (D) and other additives (E) in the presence of a solvent can be applied directly to the surface of the agricultural chemical (F) by spraying or other means using a known coating apparatus, and then dried. When the slow-dissolving coating material composition for agricultural chemicals is obtained by mixing in the absence of a solvent, the solid slow-dissolving coating material composition for agricultural chemicals can be dissolved or dispersed in a solvent as needed, and then applied to the surface of the agricultural chemical (F) by spraying or other means using a known coating apparatus, and then dried.

[0089] In the production of the slow-dissolving agricultural chemical of the present invention, the agricultural chemical (F) may be preheated. The preheating temperature of the agricultural chemical is preferably 35-60°C, or 38-50°C. In the production of the slow-dissolving agricultural agent of the present invention, the temperature of the air supplied during spraying can also be adjusted. The air supply temperature is preferably, for example, 35-60°C or 38-50°C. In the production of the slow-dissolving agricultural agent of the present invention, the pulse pressure during spraying is preferably about 0.2 to 0.5 MPa. In the production of the slow-dissolving agricultural agent of the present invention, the drying temperature after spraying is preferably around 10 to 120°C. The slow-dissolving agricultural agent of the present invention is particularly useful as an agricultural agent for spraying on fields and paddy fields. [Examples]

[0090] The present invention will be described in more detail below with reference to the following examples, but the present invention is not limited thereto. Unless otherwise specified, parts refer to parts by weight.

[0091] The composition and symbols of the raw materials used in the examples are as follows: <Ester group-containing thermoplastic resin (A)> (A-1): Polybutylene succinate [BioPBS FZ91, manufactured by Mitsubishi Chemical Corporation, Mn 80000, ester group concentration 0.50g / g, relative crystallinity 22%, SP A 10.9(cal / cm 3 ) 1 / 2 , glass transition temperature -22°C] (A-2): Polybutylene adipate terephthalate [Ecoflex (registered trademark) F Blend C1200, manufactured by BASF SE, Mn 85000, ester group concentration 0.42g / g, relative crystallinity 30%, SP A 11.1(cal / cm 3 ) 1 / 2 , glass transition temperature -45°C] (A-3): Polybutylene succinate adipate [BioPBS FD92, manufactured by Mitsubishi Chemical Corporation, Mn 75000, ester group concentration 0.47g / g, relative crystallinity 4%, SP A 10.7(cal / cm 3 ) 1 / 2 , glass transition temperature -40°C] (A-4): Polybutylene succinate terephthalate (produced in Production Example 1) [Mn 55000, ester group concentration 0.52g / g, relative crystallinity 2%, SP A 10.9(cal / cm 3 ) 1 / 2 , glass transition temperature -30°C]

[0092] <Dispersant (B)> (B-1): Compound produced in Production Example 1 [number average molecular weight 3000] (B-2): Compound produced in Production Example 2 [number average molecular weight 3000] (B-3): Compound produced in Production Example 3 [number average molecular weight 2000] (B-4): Compound produced in Production Example 4 [number average molecular weight 30000] (B-5): Compound produced in Production Example 5 [number average molecular weight 1500] (Comparative B-1): Compound produced in Production Example 6 [number average molecular weight 790]

[0093] <Organically modified layered silicate (C)> (C-1): Organic montmorillonite ["Kunibis (registered trademark) 217", manufactured by Kunimine Industries Co., Ltd., median diameter 10-20 μm, organic onium ion: dimethyldistearylammonium (38 carbon atoms), SP value of organic onium ion 8.2 (cal / cm²)] 3 ) 1 / 2 ] (C-2): Organic montmorillonite ["Kunibis (registered trademark) 127", manufactured by Kunimine Industries Co., Ltd., median diameter 10-20 μm, organic onium ion: benzyldimethylstearylammonium (27 carbon atoms), SP value of organic onium ion 8.5 (cal / cm²)] 3 ) 1 / 2 ] (C-3): Organic mica ["Somasif MAE", manufactured by Katakura Coop Agri Co., Ltd., median diameter 10-20 μm, organo-onium ion: dimethyldistearylammonium (27 carbon atoms), SP value of organo-onium ion 8.2 (cal / cm³)] 3 ) 1 / 2 ] (C-4): Organic Bentonite ["Esben NX", manufactured by Hojun Co., Ltd., median diameter 20 μm, organo-onium ion: dimethyldistearylammonium (38 carbon atoms), SP value of organo-onium ion 8.2 (cal / cm²)] 3 ) 1 / 2 ]

[0094] <Biodegradable regulator (D)> <Wax (D3)> (D3-1): Rice wax ["Rice Bran Wax XECO-0002B", manufactured by Nippon Seiro Co., Ltd., SP8.6 (cal / cm 3 ) 1 / 2 [Melting point 87℃] (D3-2): Carnauba wax [Refined carnauba wax No. 1 powder, manufactured by Nippon Wax Co., Ltd., SP8.6 (cal / cm²)] 3 ) 1 / 2 [Melting point 80-85℃] (D3-3): Mixture of behenyl behenate and behenic acid ["Unistar M222SL", manufactured by NOF Corporation, SP 8.9 (cal / cm²)] 3 ) 1 / 2 [Melting point 70℃]

[0095] <Other additives (E)> (E-1): Paraffin wax ["Paraffin Wax-145", manufactured by Nippon Seiro Co., Ltd., melting point 63°C, number average molecular weight 550] (E-2): Paraffin wax ["HNP-9", manufactured by Nippon Seiro Co., Ltd., melting point 75°C, average molecular weight 500] (E-3): Microcrystalline wax ["Hi-Mic-1090", manufactured by Nippon Seiro Co., Ltd., melting point 88°C, number average molecular weight 800] (E-4): Talc ["Micro Ace SG-95", manufactured by Nippon Talc Co., Ltd.] (E-5): Mica ["SJ-005", manufactured by Yamaguchi Mica Co., Ltd.]

[0096] <Agricultural chemicals (F)> (F-1): Urea [particle size 2.0~4.0 mm, weight-average particle size 3.3 mm, circularity coefficient 0.9] (F-2): Compound produced in Production Example 7 [particle size 2.0-4.0 mm, weight-average particle size 3.3 mm, circularity coefficient 0.9] (F-3): Compound produced in Production Example 8 [particle size 2.0-4.0 mm, weight-average particle size 3.3 mm, circularity coefficient 0.9]

[0097] Manufacturing Example 1 [Manufacturing of Dispersant (B-1)] 95.9 parts of (A-1) and 4.1 parts of 1,4-butanediol were charged into a glass polymerization tube equipped with a stirring blade, a vacuum port, and a nitrogen inlet, and the system was subjected to a nitrogen atmosphere by nitrogen-vacuum displacement. Next, the system was heated to 185°C while stirring and held for 60 minutes to carry out the transesterification reaction and obtain (B-1). The number-average molecular weight of (B-1) was 3000.

[0098] Manufacturing Example 2 [Manufacturing of Dispersant (B-2)] 95.9 parts of (A-2) and 4.1 parts of 1,4-butanediol were charged into a glass polymerization tube equipped with a stirring blade, a vacuum port, and a nitrogen inlet, and the system was subjected to a nitrogen atmosphere by nitrogen-vacuum displacement. Next, the system was heated to 185°C while stirring and held for 60 minutes to carry out the transesterification reaction and obtain (B-2). The number-average molecular weight of (B-2) was 3000.

[0099] Manufacturing Example 3 [Manufacturing of Dispersant (B-3)] 30.7 parts of ethylene glycol and 69.3 parts of adipic acid were charged into a glass polymerization tube equipped with a stirring blade, a vacuum port, and a nitrogen inlet, and the system was subjected to a nitrogen atmosphere by nitrogen-vacuum displacement. Next, the system was heated to 185°C while stirring and held for 30 minutes. Then, the temperature was raised to 220°C over 1 hour and 30 minutes, and the water produced by the reaction was removed by distillation to carry out the esterification reaction. The temperature was raised to 230°C over 1 hour, and at the same time, the pressure was gradually reduced to 0.5 mmHg over 1 hour and 30 minutes. The reaction was carried out for 4 hours after reaching 230°C to obtain (B-3). The number-average molecular weight of (B-3) was 2000.

[0100] Manufacturing Example 4 [Dispersant (B-4)] 68.6 parts succinic acid, 52.9 parts 1,4-butanediol, and 0.1 parts tetrabutyl titanate were charged into a glass polymerization tube equipped with a stirring blade, a vacuum port, and a nitrogen inlet, and the system was subjected to a nitrogen atmosphere by nitrogen-vacuum displacement. Next, the system was heated to 185°C while stirring and held for 30 minutes. Then, the temperature was raised to 220°C over 1 hour and 30 minutes, and the water produced by the reaction was removed by distillation to carry out the esterification reaction. The temperature was raised to 230°C over 1 hour, and at the same time, the pressure was gradually reduced to 0.5 mmHg over 1 hour and 30 minutes. The reaction was carried out for 4 hours after reaching 230°C to obtain (B-4). The number-average molecular weight of (B-4) was 30,000.

[0101] Manufacturing Example 5 [Manufacturing of Dispersant (B-5)] Dispersant (B-5) was obtained by charging 100 parts of gesyl alcohol, 23 parts of dodecanediol, and 46 parts of sebacic acid into a simple pressurized reactor and reacting them under the same conditions as in Production Example 1. The number-average molecular weight of (B-5) was 1500.

[0102] Manufacturing Example 6 [Manufacturing of Dispersant (Ratio B-1)] 100 parts behenyl alcohol and 31 parts sebacic acid were charged into a simple pressurized reaction apparatus, stirred while passing nitrogen gas through, and the temperature was gradually raised to 230°C under atmospheric pressure. The reaction was then carried out at 230°C for 10 hours. Next, the pressure was gradually reduced at the same temperature and the reaction was carried out at 760-40 mmHg for 10 hours to obtain a dispersant (Ratio B-1). The number-average molecular weight of (Ratio B-1) was 790.

[0103] Manufacturing Example 7 [Manufacturing of agricultural chemicals (F-2)] 50 g of biodegradable regulator (D3-1) was dissolved or dispersed in 0.5 L of trichloroethylene. Then, using a fluidized bed coating apparatus [Spiraflow SFC-LABO, manufactured by Freund], 800 g of urea (F-1) was sprayed and dried under the following conditions to obtain slow-dissolving agricultural chemical (F-2). • Agricultural chemicals (F) Preheating temperature: 40℃ • Intake air temperature: 50℃ • Pulse pressure: 0.3 MPa

[0104] Manufacturing Example 8 [Manufacturing of agricultural chemicals (F-3)] 50 g of additive (E-1) was dissolved or dispersed in 0.5 L of trichloroethylene. Then, using a fluidized bed coating apparatus [Spiraflow SFC-LABO, manufactured by Freund], 800 g of urea (F-1) was sprayed and dried under the following conditions to obtain a slow-soluble agricultural agent (F-3). • Agricultural chemicals (F) Preheating temperature: 40℃ • Intake air temperature: 50℃ • Pulse pressure: 0.3 MPa Furthermore, agricultural chemicals (F-2) and (F-3) are formed by applying a protective layer to the surface of agricultural chemical (F-1) (urea), and the quantities of agricultural chemicals (F-2) and (F-3) shown in Table 1 are merely the quantities equivalent to agricultural chemical (F-1) within (F-2) and (F-3).

[0105] <Example 1> A mixture was prepared by dissolving or dispersing (A-1) 39.5 parts, (A-2) 0.1 parts, (B-1) 0.4 parts, (C-1) 20 parts, and (D3-1) 40 parts in 1 L of trichloroethylene using a stirrer to make a total of 100 parts (100 g). Next, a 20cm x 20cm x 0.5cm glass plate was placed on a hot plate heated to 50°C, and 50μm thick masking tape was applied to both ends of the top surface of the glass plate. While drawing in 45°C hot air parallel to the glass plate at a distance of 5cm from the glass, 5g of the above mixture was poured between the masking tapes applied to both ends of the glass plate, and the mixture was made uniform using a glass rod. After that, the mixture was cast and left to stand for 10 minutes to allow any remaining solvent to evaporate, thereby obtaining a film of a slow-dissolving agricultural chemical coating composition (X-1).

[0106] <Examples 2-12, Comparative Examples 1-2> Except for using the blending raw materials (parts) shown in Table 1 in a total of 100g, the same procedure as in Example 1 was followed, and films of each film-like agricultural chemical coating composition (X) were obtained by casting and volatilizing the residual solvent.

[0107] [Table 1]

[0108] Table 1 shows the weight ratio of (A) to (B) [(A) / (B)] in each (X) obtained in the examples, the aromatic ring concentration of (A) (mmol / g), and the melt flow rate of (X) measured by the method described above (g / 10 min). Table 1 also shows the results of measuring and evaluating moisture permeability, biodegradability (degree of decay), and coating film smoothness using the methods described below. Furthermore, biodegradability (degree of disintegration), smoothness of the coating film, and moisture permeability are evaluated on the film of the coating material composition (X), while the remaining evaluations are performed on the slow-soluble agricultural chemical (Y). The biodegradability of the coating material composition is almost directly reflected in the biodegradability of the coating layer (L) of the slow-soluble agricultural chemical.

[0109] (1) Biodegradability (degree of disintegration) of the coating material composition The films of each coating composition obtained in the examples were sheared to a thickness of 15 mm × 15 mm × each film thickness, and the degree of decay (%) was measured in accordance with JIS K6954. The degree of decay (weight loss rate) (%) after 30 days at 60°C was evaluated according to the following criteria. <Evaluation Criteria> ◎: 80% or more ○: 60% or more but less than 80% △: 10% or more but less than 60% ×: Less than 10%

[0110] (2) Smoothness of the cast film of the coating material composition The films of each coating composition obtained in the examples were measured using a laser microscope [OLS5100, Olympus Corporation], and the standard deviation of the height distribution (Sq), a parameter used to evaluate the magnitude of the surface irregularities, was obtained. This (Sq) was evaluated according to the following criteria. <Evaluation Criteria> ◎: Less than 0.50 ○: 0.50 or more and less than 0.75 △: 0.75 or higher and less than 1.00 ×: 1.00 or higher

[0111] (3) Moisture permeability of the coating material composition The films of each coating composition obtained in the examples were used as measurement samples, and the moisture permeability (unit: g / m³) was measured according to the moisture permeability cup method (JIS Z0208-1976). 2 The measurement was taken over 24 hours.

[0112] <Example 21> 100 g of a slow-dissolving agricultural chemical coating composition (X-1) was dissolved or dispersed in 1 L of trichloroethylene. Then, using a fluidized coating apparatus with a jet bed [Spiraflow SFC-LABO, manufactured by Freund GmbH], 800 g of urea (F-1) was sprayed and dried under the following conditions to obtain a slow-dissolving agricultural chemical (Y-1). • Agricultural chemicals (F) Preheating temperature: 40℃ • Intake air temperature: 50℃ • Pulse pressure: 0.3 MPa

[0113] <Examples 22-32> Each slow-dissolving agricultural agent (Y) was obtained in the same manner as in Example 21, except that the raw materials (g) shown in Table 2 were used.

[0114] [Table 2]

[0115] Table 2 shows the results of measuring and evaluating the slow solubility (initial dissolution rate and 80% dissolution days), impact resistance, adhesion prevention, and fluidity of each (Y) obtained in the examples using the following methods.

[0116] (4) Slow dissolution of the drug 50g of each (Y) and 100g of deionized water were placed in a wide-mouthed glass sample bottle that could be sealed, and stored in a constant temperature bath at 25°C. The solution was stirred at regular intervals, and approximately 1g was sampled. The urea contained in the sampled solution was quantified using a liquid chromatography-mass spectrometer (LC / MS). <Measurement conditions> Equipment: LCMS-8030 (manufactured by Shimadzu Corporation) Column: Inert Sustain C18 (silica gel particle size 2 μm, inner diameter 2.1 mm, length 100 mm) Column temperature: 40℃ Mobile phase A: 10 mM ammonium acetate aqueous solution / methanol = 80 / 20 Mobile phase B: methanol Flow rate: 0.2ml / min

[0117] <Evaluation Method> <1> Initial dissolution rate (%): The elution rate was defined as the rate after 5 days of storage in a constant temperature bath at 25°C. The initial elution rate (%) was calculated using the following formula and evaluated according to the following criteria. Initial elution rate (%) = {Weight fraction of urea in the sample solution after 5 days of storage in a constant temperature bath at 25°C / Weight fraction of urea in the sample solution if all of the urea contained in the slow-dissolving agricultural chemical (Y) were to elute} × 100 [Evaluation Criteria] ◎: 5% or less 〇: More than 5% but less than 20% △: More than 20% but less than 50% ×: More than 50%

[0118] <2> 80% dissolution days (days): The number of days until 80% by weight of the urea contained in each (Y) before the test was eluted was determined according to the following criteria. [Evaluation Criteria] ◎: 60 days or more 〇: 40 days or more and 59 days or less △: 30 days or more and 39 days or less ×: 29 days or less

[0119] (5) Impact resistance 500g of each slow-dissolving agricultural chemical (Y) was scattered onto a concrete surface from a height of 100cm using a shoulder-mounted electric granule spreader (product name "Brocast Jr," manufactured by Mukai Kogyo Co., Ltd.). 50g of the scattered (Y) was used as a sample for the above analysis. <1> Similarly, the initial leaching rate (%) was measured and calculated. If cracks or chips occur in the coating layer due to impact during application to a concrete surface, the initial leaching rate <1> Since it becomes larger than the following, the difference ΔA in the initial dissolution rate before and after spraying was calculated using the following formula, and the impact resistance was evaluated according to the following criteria. ΔA(%) = {Initial elution rate of (Y) after spraying (%)} - {Before spraying (above) <1> Initial dissolution rate (%) of (Y) [Evaluation Criteria] ◎: 5% or less ○: More than 5% and less than 10% △: More than 10% but less than 20% ×: More than 20%

[0120] (6) Anti-sticking properties Agricultural chemical adhesion is a phenomenon in which granules of agricultural chemicals adhere to each other at contact points, forming clumps that worsen the application (sprayability) of the chemical. Furthermore, if uniform application is not possible, it can have adverse effects such as variations in efficacy. In this invention, adhesion prevention performance is evaluated based on the adhesion rate (%) determined by the following method. Three bags were prepared, each containing 100g of (Y). The three bags were stacked, a wooden board was placed on top of the top bag, and a 3kg weight was placed on top of the wooden board to apply load. The bags were left undisturbed for one month under conditions of 25°C and 50% humidity. After one month, (Y) was removed from the middle bag of the stack, and the total weight (g) of the aggregated particles (3 or more particles adhering together) was measured. The adhesion rate (%) was calculated using the following formula, and the adhesion prevention performance was evaluated according to the following criteria. Adhesion rate (%) = {(Total weight of adhering particles after 1 month [g]) / 100 [g]} × 100 [Evaluation Criteria] ◎: 20% or less ○: More than 20% but less than 40% △: More than 40% but less than 60% ×: More than 60%

[0121] (7) Liquidity The fluidity of each (Y) was measured using a funnel-shaped orifice tube, referencing JIS Z2502 (Method for Measuring the Fluidity of Metal Powders). Higher fluidity tends to improve the handling (application, etc.) of agricultural chemicals. A funnel-shaped orifice tube was prepared with an orifice diameter of 12 mmφ, an orifice length of 55 mm, an upper end diameter of 75 mmφ, and a funnel-shaped section length of 50 mm. It was fixed vertically using a support stand. With the orifice closed, 50 g of (Y) was placed into the funnel-shaped section. As the orifice was opened, a stopwatch was started and the time (seconds) until the entire amount came out of the orifice tube was measured. The flow rate (seconds / g) was calculated as the particle drop time per unit weight. Three measurements were taken for each (Y), and the arithmetic mean was calculated to evaluate the flow rate according to the following criteria. [Evaluation Criteria] ◎: 1.0 seconds / g or less ○: More than 1.0 seconds / g but less than 1.5 seconds / g △: More than 1.5 seconds / g but less than 2.0 seconds / g ×: More than 2.0 seconds / g

[0122] (8) Uniformity of coating thickness A slow-dissolving agricultural chemical was cut in half with a razor blade, passing through its center of gravity. The cross-section was photographed using a scanning electron microscope (SEM), and the thickness (μm) of the coating layer (L) at any one location was measured. Five particles were randomly selected, cut in the same manner, and the thickness of the coating layer (L) was measured. The average thickness of the coating layer (L) of the five particles was taken as the average coating layer (L) thickness (μm). The difference between the average thickness and the maximum and minimum thicknesses was used to evaluate the averageness of the film thickness according to the following criteria. ◎: Within ±10% of the average value ○: Within ±30% of the average value △: Within ±50% of the average value ×: More than 50% from the average. [Industrial applicability]

[0123] The slow-dissolving agricultural chemical coating composition of the present invention achieves a high level of control over both the biodegradability of the coating layer and the slow dissolution of the chemical, and provides a slow-dissolving agricultural chemical with excellent impact resistance, anti-adhesion properties, and fluidity. Therefore, it can be suitably used as a coating layer for agricultural chemicals (fertilizers, pesticides, and pest control agents, etc.), especially for agricultural chemicals sprayed on fields and paddy fields, and is useful.

Claims

1. A slow-dissolving coating material composition for agricultural chemicals, comprising an ester group-containing thermoplastic resin (A) and a dispersant (B), wherein the ester group-containing thermoplastic resin (A) has a number average molecular weight of 50,000 to 500,000, and the dispersant (B) is a polyester oligomer with a number average molecular weight of 1,500 to 30,000.

2. Furthermore, a slow-dissolving agricultural chemical coating composition containing organic layered silicate (C).

3. Furthermore, the slow-dissolving agricultural chemical coating composition according to claim 1, comprising a biodegradation regulator (D).

4. The slow-dissolving agricultural chemical coating composition according to claim 1, wherein the weight ratio [(A) / (B)] of the ester group-containing thermoplastic resin (A) to the dispersant (B) is 99 / 1 to 70 / 30.

5. The slow-dissolving agricultural chemical coating composition according to claim 1, wherein the aromatic ring concentration of the ester group-containing thermoplastic resin (A) is 0.001 to 2.250 mmol / g.

6. The slow-dissolving agricultural chemical coating composition according to claim 1, wherein the melt flow rate (MFR) of the slow-dissolving agricultural chemical coating composition at 190°C and a 10 kg load is 0.01 to 300 g / 10 min.

Citation Information

Patent Citations

  • Coated granular fertilizer coated with decomposable film

    JP1993201786A